Skin signs of primary immunodeficiencies: how to find the genes to check. (14th February 2018) - Ettinger, M.; Schreml, J.; Wirsching, K.; Berneburg, M.; Schreml, S.
Summary: Primary immunodeficiencies are rare chronic disorders, in which parts of the immune system either lack or function improperly. Thus, the immune system is weakened, and patients are more susceptible to germs that can cause infections. Patients can have various symptoms, but all have repeated prolonged and/or serious infections, sometimes from uncommon germs. Half of the patients have symptoms on their skin, which can help a doctor to recognize the underlying immune disorder. Therefore, the authors of this study provide a table to make it easier for the physician to diagnose an immune disorder according to the skin signs once an immunodeficiency is suspected. They list typical skin manifestations and the according diseases and genes to check. Abstract : Linked Article: Ettinger et al. Br J Dermatol 2018;178 :335–349